Monitoring of pregnancies with successful deliveries in a Niemann-Pick disease type B patient - case report and literature review - Agić Danijela; Milošević Ivana; Mitić Gorana; Kavečan Ivana; Stojić Siniša (Srpski Arhiv za Celokupno Lekarstvo, 2023)
Introduction. Niemann–Pick disease type B is an autosomal recessive disease caused by sphingomyelinase deficiency resulting in sphingomyelin accumulation in macrophages of various organs. Visceral involvement includes spleen enlargement, thrombocytopenia, dyslipidemia, sphingomyelin deposition in lung and liver, and bleeding risk. This is a rare disease and literature data about pregnancy in this setting are scarce. We present two favorable pregnancy outcomes in a patient with Niemann–Pick disease type B along with the review of the literature. Case outline. At the time of the first intended pregnancy, the patient was 34 years old. She had an extremely enlarged spleen, mild restrictive pulmonary disorder, hyperlipoproteinemia type IIb, thrombocytopenia with impaired aggregation tests. Cesarean section was indicated. She was prepared for delivery with platelet concentrates and prophylactic use of antibiotics. In the 36th week of gestation, a Cesarean section without complications was performed. The newborn’s anthropometric parameters were BW 2490, BL 47 cm, HC 32 cm, and Apgar score was 7/8. The infant’s development was normal. Three years later, in the second wanted pregnancy, the same examinations were done. The planned Cesarean section was done without complication after the same procedures, including prophylactic use of antibiotics and platelet concentrates, and a healthy female child was born. Conclusion. A multidisciplinary approach in female patients who suffer from lysosomal storage disease such as Niemann–Pick disease type B is essential and a favorable course is possible despite all risks.